Rare bird documentation form for Bohemian Waxwing at Oak Grove Recreation Area at Saylorville Reservoir, 1986 - Dinsmore, Stephen J.et al (1986)
Rare bird documentation form for a Bohemian Waxwing at Oak Grove Recreation Area at Saylorville Reservoir in Polk County, IA on November 23, 1986. Epson - sheet feed